Analisis Praktik Etika Teknisi Akuntansi: Studi Kasus Pada Koperasi Simpan Pinjam Pembiayaan Syariah Muamalah Berkah Sejahtera [MBS] Surabaya - Naja Dewi, Sephia; Subandoro, Agus (CV. Lafadz Jaya, 2022)
The purpose of the research was to determine the ethical practice of accounting technicians at the MBS Sharia Savings and Loans Financing Cooperative (Muamalah Berkah Sejahtera) Surabaya. In this research, the authors assessed the activities related to accounting and the daily behavior of technicians. Qualitative descriptive including the type of research used. Observations, interviews and documents to obtain data from the MBS Sharia Savings and Loans Financing Cooperative. The analysis used in this research was carried out in three stages, namely data reduction, data presentation, and examination. The results obtained are that there are various unethical and ethical behaviors carried out by accounting technicians. ethical behavior is shown by way of solving problems in a family way or deliberation by accountants, technical with effective solutions, technical who always trusts its members, correct and good technical in carrying out their duties. Meanwhile, unethical technicians, such as not being transparent to prospective members and job exchanges or doing work that is not in accordance with the organizational structure.